2010
DOI: 10.1007/s10967-010-0802-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of labelled products with different radioanalytical methods: study on 18F-fluorination reaction of 4-[18F]fluoro-N-[2-[1-(2-methoxyphenyl)-1-piperazinyl]ethyl-N-2-pyridinyl-benzamide (p-[18F]MPPF)

Abstract: The serotonin receptor 5-HT 1A ligand 4-[

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For [ 18 F]MPPF, the nondisplaceable binding potential was calculated in target regions from the entire scan period using the Logan linear graphical method with the cerebellum as a reference tissue input. MPPF has a low radiochemical yield, and as a result of issues with tracer production, the injected specific activity in a number of animals was considered insufficient, resulting in a total number of 10 (three naive, four sham, and three animals with epilepsy). A detailed description of the μPET procedure can be found in .…”
Section: Methodsmentioning
confidence: 99%
“…For [ 18 F]MPPF, the nondisplaceable binding potential was calculated in target regions from the entire scan period using the Logan linear graphical method with the cerebellum as a reference tissue input. MPPF has a low radiochemical yield, and as a result of issues with tracer production, the injected specific activity in a number of animals was considered insufficient, resulting in a total number of 10 (three naive, four sham, and three animals with epilepsy). A detailed description of the μPET procedure can be found in .…”
Section: Methodsmentioning
confidence: 99%
“…reported that the preparative HPLC conditions described by Le Bars et al . failed occasionally to separate p ‐[ 18 F]MPPF from the radioactive by‐products with close retention time because the crude p ‐[ 18 F]MPPF in DMSO was diluted with the mobile phase and injected straight into an HPLC system . In contrast, we diluted the crude p ‐[ 18 F]MPPF in DMSO with 20% MeCN(aq) and injected it straight into an HPLC system.…”
Section: Resultsmentioning
confidence: 99%
“…, which is used as a PET tracer for the evaluation of the 5-HT 1A serotonin receptor, 19,20 was also investigated using our newly developed microwave system (Table 3). [ and K 2 CO 3 at 180°C for 10 min gave [ 18 F]MPPF in a 26% yield (Table 3, entry 1), whereas microwave heating gave the product in 74% yield (Table 3, entry 2).…”
Section: Introductionmentioning
confidence: 99%